The redistributive effects of tax benefit systems in the enlarged EU - Clemens Fuest; Judith Niehues; Andreas Peichl (Institute for the Study of Labor (IZA), 2009)
How do different components of the tax and transfer systems affect disposable income inequality? This paper explores the redistributive effects of different tax benefit instruments in the enlarged EU based on two approaches. Inequality analysis based on the standard approach suggests that benefits are the most important factor reducing inequality in the majority of countries. The factor source decomposition approach, however, suggests that benefits play a negligible role and sometimes even contribute slightly positive to inequality. On the contrary, here taxes and social contributions are by far the most important contributors to income inequality reduction. We explain these partly contradictory results with the different normative focus of the two approaches and show that benefits have other aims than redistribution. Finally, our country clustering shows that the Eastern European countries do not form a distinguished group. The Central Eastern European countries group together with the Continental European countries and the Baltic States show similarities with some Southern European countries.
urn:nbn:de:101:1-20091105910
Keywords: D31; D60; H20; 330; Inequality; redistribution; decomposition; tax benefit systems; Steuersystem; Sozialtransfer; Verteilungswirkung; Verfügbares Einkommen; Einkommensverteilung; EU-Staaten; EU-Staaten (Osteuropa); Südeuropa